Optimalisasi Mesin Cetak Pelet dalam Pembuatan Pilus Cita Rasa Ikan Lele - Mohammad Nurhilal; Saiful Bahri; Taufan Ratri Harjanto (Caradde, 2020)
The purpose of the community dedication program carried out in the Karya Rasa Lestari group is to make a snack product the pilus of catfish flavor. The implementation of this program goes through three stages: the interview stage with partners, literature study through literature review to get the type of mold machine, and training in making Pilus using the molding machine. Based on the literature review, it was found that a molding machine suitable for making Pilus was a vertical type mold machine. The result of the vertical type Pilus mold machine with a capacity of 100 kgs/hour with a diesel engine driving the capacity of 8 Hp. The result of the molding machine has a uniform shape according to the shape of the Pilus which is proven through the training of making Pilus with the taste of catfish. Produce fish taste in Pilus by adding catfish mixed with other ingredients. This Pilus food product is intended to increase the type of processed fish food business in the Karya Rasa Lestari group which will be produced in the future